LEVEL OF PUBLIC KNOWLEDGE ABOUT DAGUSIBU IN BANJAR BATAN POH PANDAK GEDE KEDIRI TABANAN VILLAGE: TINGKAT PENGETAHUAN MASYARAKAT TENTANG DAGUSIBU DI BANJAR BATAN POH DESA PANDAK GEDE KEDIRI TABANAN - Iwan Saka Nugraha; Ni Wayan Devi Wiryani (Institut Teknologi dan Kesehatan Bintang Persada, 2022)
Dagusibu (Get, use, save and throw away) is a health education program created by IAI in an effort to realize the Drug Awareness Family Movement as a concrete step to improve the quality of life of the community. This study aims to determine the level of public knowledge about Dagusibu medicine in Banjar Batan Poh, Pandak Gede Village, Kediri, Tabanan. This type of research is descriptive research. The research population is all people living in Banjar Batan Poh, Pandak Gede Village, Kediri District, Tabanan Regency as many as 289 families. The sample is housewives from each head of the family as many as 82 respondents. The sampling technique used a simple random sampling approach. The results showed that the level of public knowledge about Dagusi-bu medicine in Banjar Batan Poh, Pandak Gede Village, Kediri, Tabanan was in a fairly good condition which can be seen from the results of the analysis of respondents' knowledge about Dagusibu with the highest percentage of 46.3%. Factors that influence people's knowledge about Dagusibu medicine in Banjar Batan Poh, Pandak Gede Village, Kediri, Tabanan are age level, education level, occupation and level of knowledge possessed by the community. This can be seen from the results of the analysis in terms of the age level of 25-35 years (45.7%) having good knowledge, in terms of the latest education in higher education, having a good knowledge level of 48.6% and a good level of knowledge in the community who work as civil servants/private sector is 54.3%.